2022
DOI: 10.3390/ijerph19159322
|View full text |Cite
|
Sign up to set email alerts
|

University Students’ Mental Health and Well-Being during the COVID-19 Pandemic: Findings from the UniCoVac Qualitative Study

Abstract: The worldwide spread of the coronavirus disease 2019 (COVID-19) pandemic in early 2020 affected all major sectors, including higher education. The measures to contain the spread of this deadly disease led to the closure of colleges and universities across the globe, disrupting the lives of millions of students and subjecting them to a new world of online learning. These sudden disturbances coupled with the demands of a new learning system and the experiences of living through a pandemic have placed additional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 56 publications
1
28
0
4
Order By: Relevance
“…For programs with limited support staff and budgets, careful preparation would be needed to tackle the technical and financial issues that will arise. Although a concern, the emergence of mental health issues in this study was similar to that found in several other recent studies, with slight differences in details depending on academic institution and region [ 14 , 17 , 18 , 19 , 20 , 21 ]. Interestingly, prior to such recent studies involving the influence of COVID-19 responses to the mental health of student bodies at academic institutions, much of the discussion focused on the benefits of online curricula.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…For programs with limited support staff and budgets, careful preparation would be needed to tackle the technical and financial issues that will arise. Although a concern, the emergence of mental health issues in this study was similar to that found in several other recent studies, with slight differences in details depending on academic institution and region [ 14 , 17 , 18 , 19 , 20 , 21 ]. Interestingly, prior to such recent studies involving the influence of COVID-19 responses to the mental health of student bodies at academic institutions, much of the discussion focused on the benefits of online curricula.…”
Section: Discussionsupporting
confidence: 89%
“…The literature suggests Academic stakeholders are susceptible to impacts involving health, sociology, and achievement [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 31 , 32 , 33 , 34 , 35 ]. The generalization of Health as being the overall physical, mental, and emotional condition with regards to academic activities relevant to the individual.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations